Comparison of Angiotensin Converting Enzyme Inhibitors and Beta Blockers in Prevention of Atrial Fibrillation Recurrences After Electrical Cardioversion - Timuçin Altın; Adalet Gürlek; Çağdaş Özdöl; Mustafa Kılıçkap; İrem Dinçer; Sibel Turhan; Çetin Erol (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim: Angiotensin-converting enzyme (ACE) inhibitors and beta blockers were shown to be effec-tive in prevention of atrial fibrillation (AF) recurrences after electrical cardioversion, by interfering with atrial structural and electrical remodeling. In this study, we aimed to compare the effects of ACE inhibitor cilazapril and beta blocker metoprolol after cardioversion of AF in terms of sinus rhythm maintenance.Patients and Methods: The study population comprised 120 patients with persistent atrial fibril-lation (>7 days) who underwent successful cardioversion. Randomization into 3 groups was done after successful cardioversion. Group I (n=41) was treated with amiodarone, group II (n=41) was treated with amiodarone plus metoprolol, and group III (n=38) was treated with amiodarone plus cilazapril. The primary end-point of the study was the recurrence rates between groups at one year and with those who recurred, the time to recurrence of AF.Results: After 1 year follow-up, maintenance of sinus rhythm were similar among groups (Kaplan-Meier analysis, 24%, 37% and 26% respectively; log rank=0.3). There was no difference among groups with respect to time to recurrence of AF.Conclusion: Patients treated with amiodarone only, amiodarone plus metoprolol and amiodaro-ne plus cilazapril had similar rates of recurrence of AF.